Peningkatan Pemahaman dan Praktik Filantropi Islam melalui Pengabdian kepada Masyarakat Bandar Selamat - Dalimunthe, Kariamin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Lhokseumawe, 2023)
This community service aims to provide education on the management of philanthropy according to Islamic law. The objective is to benefit participants in understanding the practical aspects of managing household finances in accordance with Sharia, thereby contributing to the government's community empowerment programs. The research employs a qualitative approach, focusing on the understanding and behavioral changes within the community. Data is collected through direct engagement with sources during the implementation of the community service activities. The collection techniques include: 1) Interviews with key informants and participants, 2) Observations of activities, and 3) Documentation studies. The primary data sources are the informants and members of the